AN ECONOMETRIC ANALYSIS OF CONSUMER DEMAND FOR COCONUTS IN SRI LANKA - S. R. Samarajeewa (International Coconut Community Journal, 2002)
This study analyses the domestic demand for coconuts in Sri Lanka using a single equation econometric model. The domestic coconut consumption accounts 70 percent of the total annual nut production in Sri Lanka. Being an essential commodity for household use, the coconuts form a stable domestic market out-let for producers as well. The results of the study reveals that the retail price of coconuts and per capita consumer income are significant variables that determine the quantity of coconut demand in Sri Lanka. There is a significant negative trend in per capita consumption of coconuts over time, indicating a declining tastes and preferences by the consumer. However, the changes in consumer demand for coconuts to the changes in retail prices are less responsive as indicated by the lower own price elasticity value of –0.11. The income elasticity of coconut demand is 0.38 and it is inelastic too.